Empoderamento do paciente na redução de eventos adversos em um hospital universitário - Alves, Valdelanda de Paula (2020)
Introduction: Adverse events (AE) are any occurrence unfavorable to the patient and that does not necessarily have a causal relationship with the treatment, being considered a marker of the quality of care provided by the health team. There is a need to clarify the evidence on the effect of patient education on reducing adverse events, as well as conducting national studies in this subject. The situational diagnosis at HUGV/AM, in the period between 2015 and 2018, accounted for a total of 749 adverse events, including one death, called Never Events, an event that was not supposed to happen (VIGIHOSP, 2016), which led to the proposal search. Aims: a) to identify, through a systematic review of the literature, if the patient empowerment reduce adverse events during hospitalization; b) identify the perception of HUGV/AM professionalsaboutthepatient'sempowermentinthepreventionofadverseevents; c) analyze the effect of an intervention with soft technology on the team's routine in reducing adverse events; d) produce an educational video script that should be transmitted via the Virtual Learning Environment of the Unified Health System - AVASUS. Method: mixed method research comprising a) Study 1 - systematic literature review that delivered the specific protocol based on the PRISMA-P checklist. The search strategies were applied in the databases (Cochrane, Lilacs, PubMed, Scopus, and Web of Science) and in the gray literature (Google scholar, Open Gray and ProQuest Dissertations and Thesis). The risk of bias was assessed using the ROBBINS-I (non-randomized studies) and RoBS 2 (randomized studies) tools and a meta-analysis of the data was performed. b) Study 2 - applied case study, transversal, exploratoryanalytical research; c) Study 3 - applied research, a case study with intervention using soft technology, which included the insertion of 3 questions about the patient's empowerment in the face of adverse events in the professionals' routine form. Participants in studies 2 and 3 were professionals WHO worked in the care of adult patients admitted to the medical clinic of HUGV/AM. d) Study 4 - methodological research for the development of the video script. Quantitative descriptive, inferential, and qualitative analyzes were performed on the data obtained in the studies. Results: a) Study 1 - the inclusion / exclusion criteria were applied on 4 papers that addressed the AE “Falls” remained for final analysis in the systematic review, which demonstrated that patient education has scientific evidence for its use in reducing these adverse events; b) Study 2 - HUGV/AM professionals reported that patient empowerment is important for the prevention of adverse events, however it is necessary to work with the team to better understand the patient's safety protocols, as well as to raise their awareness for person-centered care; c) Study 3 - analyzing the pre and post intervention data in the professionals' routine form, there was a statistically significant difference in the reduction of adverse events of patient identification and falls, but not in the events of skin injury and medication administration; d) Study 4 - after reviewing the script, it is ready and will be used for the production of educational material via AVASUS. Conclusion: The empowerment of the patient and his companion reduces adverse effects during hospitalization and the proposal for interventions with light technology, such as the insertion of questions in the patient safety form and the educational video represent a low-cost possibility for minimization adverse events at HUGV / AM, which may be scalable to other hospitals. As a synthesis outcome of the study, it is clear that the changes occur in relation to adverse events within hospitals, a re-approach with all professional categories is necessary, emphasizing on the role of each one towards patient safety, disseminating the established protocols , the basics, and act in order to consider the importance of the patient for patient safety, acting as partners in their care, acting as possible barriers to avoid adverse events.